Pengaruh Kegunaan, Kepuasan Pengguna, dan Pengalaman Wisata Virtual Reality dalam Strategi Pemasaran pada Taman Bunga Celosia - Ekasari, Silvia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aimed to analyze and determine the influence of usability, user satisfaction, and virtual reality tourism experience on marketing strategies at Celosia Flower Garden. The population in this study was 250 virtual reality service users for an average period of one month. To provide accurate results, the sample size was taken using the Slovin formula. Based on this calculation, the sample size for this study was 71 respondents. The research method used was SPSS. The results showed that the usability variable had a partial positive and significant effect on marketing strategies. This is evidenced by the regression coefficient value of 0.316 (positive) with a significance value of 0.007 <0.05, thus H1 is accepted. The user satisfaction variable had a partial positive and significant effect on marketing strategies. This is evidenced by the regression coefficient value of 0.222 (positive) with a significance value of 0.009 <0.05, thus H2 is accepted. The virtual reality tourism experience variable had a partial positive and significant effect on marketing strategies. This is evidenced by the regression coefficient value of 0.392 (positive) with a significance value of 0.001 <0.05, so H3 is accepted. The variables of usability, user satisfaction and virtual reality tourism experience simultaneously have a positive and significant effect on marketing strategies. This is evidenced by the calculated F value of 25.320 > F table 3.13 and the significance value (Sig.) of 0.000 <0.05 and is positive, so H4 is accepted.